Terahertz Radiation Transport in Photonic Glasses. Issue 8 (8th July 2020) - Gentilini, Silvia; Missori, Mauro; Ghofraniha, Neda; Conti, Claudio
Abstract: Multiple scattering of electromagnetic (EM) waves arises in disordered media with a refractive index varying on the scale of the wavelength. The diffusion approximation is a powerful tool to treat multiple scattering as a photon random walk, neglecting resonant phenomena. However, as the light intensity varies on a scale much smaller than the transport mean free path, resonances may occur in media formed by finite‐size scatterers and break the diffusion approximation. The energy and phase velocity are very useful tools to reveal the onset of the resonant transport regime. In this paper the study of the propagation of terahertz (THz) waves through 3D random media by employing terahertz time‐domain spectroscopy (THz‐TDS) is addressed. Specifically, measurements of the electric field transmitted by samples of different thicknesses made of 1 mm diameter silica spheres dispersed in a paraffin matrix at different filling fractions are reported. This investigation has provided an accurate measurement of the EM field phase and, hence, information on the radiation propagation velocity that has enabled the first observation of a photonic glass at the THz range. Abstract : The propagation of terahertz waves through 3D random structures is studied by exploiting terahertz time‐domain spectroscopy. The employment of such a technique allows direct measurement of the electromagnetic field phase. This enables direct access to the radiation propagation velocity and leads to the first observation of a photonic glass at the Terahertz range.